PELAKSANAAN PEMBINAAN DAN PENGAWASAN MAJELIS PENGAWAS DAERAH TERHADAP NOTARIS DI KOTA BEKASI - , Anggita Permatasari; , Prof. Dr. Sudjito, S.H., M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research discusses on implementation of the Sub-Regional Supervision Council authority and obligation in supervising and control the Notary in Bekasi City. The purpose of this research is to investigate supervision and control by the district Supervisors Council to Notary in Bekasi City and to know the constraints or obtacles faced by the District Supervisor Council in managing the supervision and control on Notary in Bekasi City. This research is normative empirical. The Data used in this research is the primary and secondary data. The data were processed using qualitative analysis and the reasoning used to draw the conclusion is the inductive method. Based on the research conducted is found that the implementation of the supervision and control by the Sub-Regional Supervision Council on the Notaries in Bekasi City is not yet optimal that is reflected from the fact that some authorities and obligations of the Sub-Regional Supervision Council are not yet manage apporiate the regulations. The obstacles faced by the Sub-Regional Supervision Council of Bekasi City in managing the supervision and control Notaries in Bekasi City are the fund (to pay for oprational expenses and the salary of the members of the District Supervisors Council), the supporting means and facilities, time, and the unknown existence of some Notaries in Bekasi City.